The Failed-Escape Artist: Kafka, Houdini and “In the Penal Colony” - Hingley, LH (Indiana University Press, 2019)
In Kafka studies there exists an often dualistic debate: is escape from his texts possible or impossible? Scholars have not fully considered how comparing Kafka's “In the Penal Colony” with Houdini's escape art may offer a more nuanced approach. The escape artist's body could be read in the story's imagery and form to provide three new yet distinct interpretations. While the first two interpretations trace the existing debate on the (im)possibility of escaping Kafka's work, the third suggests how the failure to escape within and beyond Kafka's text constitutes its art.